2015
DOI: 10.1039/c5dt00081e
|View full text |Cite
|
Sign up to set email alerts
|

Icosahedral metallacarborane/carborane species derived from 1,1′-bis(o-carborane)

Abstract: Examples of singly-metallated derivatives of 1,1'-bis(o-carborane) have been prepared and spectroscopically and structurally characterised. Metallation of [7-(1'-1',2'-closo-C2B10H11)-7,8-nido-C2B9H10](2-) with a {Ru(p-cymene)}(2+) fragment affords both the unisomerised species [1-(1'-1',2'-closo-C2B10H11)-3-(p-cymene)-3,1,2-closo-RuC2B9H10] (2) and the isomerised [8-(1'-1',2'-closo-C2B10H11)-2-(p-cymene)-2,1,8-closo-RuC2B9H10] (3), and 2 is easily transformed into 3 with mild heating. Metallation with a prefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 49 publications
5
32
0
Order By: Relevance
“…The isomerization is presumably the result of otherwise untenable steric interaction between the mes and carborane substituents. Strong circumstantial evidence for this conclusion is that in 1 and 2 the arene ring is bent away from the carborane substituent, subtending angles of 10.57(17) and 12.56(11)° respectively with the plane through atoms B5, B9, B12, B13, and B8, and that related sterically driven isomerizations have been noted in 12‐vertex metallacarborane/12‐vertex carborane analogues …”
Section: Figuresupporting
confidence: 78%
“…The isomerization is presumably the result of otherwise untenable steric interaction between the mes and carborane substituents. Strong circumstantial evidence for this conclusion is that in 1 and 2 the arene ring is bent away from the carborane substituent, subtending angles of 10.57(17) and 12.56(11)° respectively with the plane through atoms B5, B9, B12, B13, and B8, and that related sterically driven isomerizations have been noted in 12‐vertex metallacarborane/12‐vertex carborane analogues …”
Section: Figuresupporting
confidence: 78%
“…Recent years have witnessed a significant amount of interest in the chemistry of bis(carboranes) [1][2][3][4], particularly 1,1 -bis(ortho-carborane), formally [1-(1 -closo-1 ,2 -C 2 B 10 H 11 )-closo-1,2-C 2 B 10 H 11 ] (I), Scheme 1. This species offers a versatile scaffold for derivatisation and, amongst other studies, we have reported the single deboronation/metalation [5], double deboronation/homometalation [6] and stepwise deboronation/metalation-deboronation/heterometalation [7] of I, the latter including the use of {Rh(H)(PPh 3 ) 2 } fragments to afford homogeneous catalyst precursors [8].…”
Section: Introductionmentioning
confidence: 83%
“…However, this has now been achieved 3 and consequently a significant amount of new chemistry of 1,1′-bis (o-carborane) has recently appeared. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Several authors have taken advantage of the functionality of its C cage H units to use 1,1′-bis(o-carborane) as a κ 2 ligand, binding transition-metals to the cage through two M-C σ-bonds, with recent studies 7,8,13,19 building on the pioneering work of Hawthorne and co-workers. 21 In marked contrast, very little has been reported concerning main group elements bound to 1,1′-bis(o-carborane).…”
Section: Introductionmentioning
confidence: 99%